Oceanic protection of prebiotic organic compounds from UV radiation - Cleaves, H. James (The National Academy of Sciences, 1998)
It is frequently stated that UV light would cause massive destruction of prebiotic organic compounds because of the absence of an ozone layer. The elevated UV flux of the early sun compounds this problem. This applies to organic compounds of both terrestrial and extraterrestrial origin. Attempts to deal with this problem generally involve atmospheric absorbers. We show here that prebiotic organic polymers as well as several inorganic compounds are sufficient to protect oceanic organic molecules from UV degradation. This aqueous protection is in addition to any atmospheric UV absorbers and should be a ubiquitous planetary phenomenon serving to increase the size of planetary habitable zones.